Palace traditions and culture form; the spatial structure of the Baluwarti settlement “Manunggaling Kawula Ian Gusti” - Hartanto, Tri; Dharoko, Tony Atyanto; Subroto, Tarcicius Yoyok Wahyu (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
According to Paku Buwana I, Radya Laksana is a form and core image of the culture of the Surakarta Palace. The literal meaning is physical and mental behavior to uphold the country. Its elements consist of the king, Sentana's son, courtiers, people, the physical building, government, and region. The Surakarta palace's culture is Islamic, but when it pertains to rituals and palace traditions, it has remained inextricably associated with Hindu culture. This is the belief in reciprocal relationships and parallels between the macrocosm and microcosm, where the king, as the center of the microcosm, gave rise to numerous traditional ceremonies that are practiced in the palace, including Grebeg, Kirab-Jamasan Pusaka, Labuan, Malem Selikuran, Mahesalawung, Tingalan Jumenengan Dalem, Tingalan Dalem, and Pasowanan Ngabekten. The Surakarta Palace region includes the Baluwarti village. Most of the individuals are courtiers for the king, who have the expertise required by the king and palace. The phases of the past and present are examined in this study method. Investigations into past lives are conducted through historical reading research. The data is collected through interviews with the public and observation. The results of the research show that the spatial structure of settlement forms a system of manunggaling Kawula lan Gusti.